Effect of curing temperatures on the early-age tensile creep behavior of high-performance concrete - Yuanxi Wang; Suduo Xue; Xiongyan Li; Yan Geng; Hua Rong; Xiuliang Lu (Case Studies in Construction Materials)
High-performance concrete (HPC) is prone to cracking due to significant early autogenous shrinkage. Tensile creep (TC) can effectively relieve stress restraint and mitigate crack propagation. However, the coupling effects of curing temperature and loading age on early-age TC behavior remain unclear. This study investigates the early-age TC of HPC under varying curing temperatures and loading ages. A custom-designed device was used to examine the effects of six curing temperatures and three loading ages on early-age TC under a stress intensity ratio of 0.4. The results show that higher curing temperatures improve the mechanical properties of HPC, increasing compressive strength by 23.8 % at 28 days. Although higher curing temperatures increase early autogenous shrinkage, they reduce early-age TC, especially when the loading age is 1 day. Increasing the curing temperature from 20 °C to 75 °C reduces early-age TC by approximately 60.4 %. A prediction model based on the B3 model incorporates a temperature-age correction function, quantifying the coupling effect. The goodness of fit between predicted and measured values ranges from 0.93 to 0.99, with a maximum relative error of less than 9.9 %. This study provides a theoretical foundation for the crack-resistant design of HPC structures.